2023
DOI: 10.1007/s00167-023-07330-1
|View full text |Cite
|
Sign up to set email alerts
|

Younger patients, lower BMI, complete meniscus root healing, lower HKA degree and shorter preoperative symptom duration were the independent risk factors correlated with the good correction of MME in patients with repaired MMPRTs

Abstract: Purpose To evaluate the clinical and radiological outcomes of arthroscopically assisted tendon graft anatomic reinforced reconstruction of the medial meniscus posterior root tears (MMPRTs) and identify relevant factors afecting the correction of medial meniscal extrusion (MME). Methods Fifty-three MMPRTs patients who underwent arthroscopically assisted tendon graft reconstruction of the meniscal root between 2018 and 2020 were evaluated retrospectively. the patients were divided into 2 groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…ΔMME suppression is important to reduce the progression of arthropathic changes. Patient characteristics that have been reported to be related to ΔMME include body mass index [ 16 ] and time from injury to surgery [ 17 ]. Multiple regression analysis was used to examine the relationship between these characteristics and the postoperative quadriceps muscle strength; the postoperative quadriceps muscle strength had a significant effect on ΔMME even when the body mass index and time from injury to surgery were included.…”
Section: Discussionmentioning
confidence: 99%
“…ΔMME suppression is important to reduce the progression of arthropathic changes. Patient characteristics that have been reported to be related to ΔMME include body mass index [ 16 ] and time from injury to surgery [ 17 ]. Multiple regression analysis was used to examine the relationship between these characteristics and the postoperative quadriceps muscle strength; the postoperative quadriceps muscle strength had a significant effect on ΔMME even when the body mass index and time from injury to surgery were included.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 18 demonstrated the successful use of semitendinosus tendon autograft in a rabbit model resulting in biomechanical properties that were similar to that of the normal meniscus. Additionally, compared to the transtibial pull-out technique, the arthroscopically assisted meniscus root reconstruction with gracilis autograft demonstrated advantages in treating patients, resulting in superior clinical outcomes and higher rates of meniscus root healing 19 , 20 . Like the anterior cruciate ligament model, the reinforced reconstruction technique that the initial fixation is strong enough to resist initial displacement and provide a long-term stability structure allows the tendon graft to heal the meniscus and bony tunnels 21 .…”
Section: Discussionmentioning
confidence: 99%
“…MME progression after pullout repair for MMPRTs has been reported to be influenced by various factors such as patient characteristics, surgical technique, and rehabilitation. Therefore, a consensus has not yet been reached on the extent and timing of MME progression [ 11 , 12 ]; most of the previous reports addressing MME progression after pullout repair for MMPRTs have been evaluated at one point in time or at the last follow-up.…”
Section: Introductionmentioning
confidence: 99%